Metal-Only Reflectarray Based on Polarization Conversion Element for W-Band - Bharati R.; Saurabh A.K.; Ajitesh; Meshram M.K. (My University, 2025)
A polarization rotation element based metal-only reflectarray is proposed for (W-band) spectrum. The unit cell has a double-arrow slot on a metallic sheet that has a periodicity of 1 mm (λ0/3 at 100 GHz) and thickness of 0.2mm. The required phase shift is achieved by rotating the slot on the metal sheet by ±45º. The reflectarray features a circular aperture having a diameter of 30 mm and is engineered to operate in the sub-millimeter-wave frequencies and the early terahertz spectrum. A pyramidal horn antenna that has a gain of 13 dBi at 100 GHz is used to excite the reflectarray. The focal length is 24 mm, resulting in an F/D ratio of 0.8. The reflectarray achieves a gain of 21.7 dBi with an aperture efficiency of 15% at 100 GHz. Additionally, it features a 3-dB gain bandwidth of the aperture spans 14%, covering frequencies from 93 GHz to 107 GHz, underscoring its capability for early THz applications. © 2024 IEEE.